Chapter 2 - A self-assessment, and a tutorial in Excel - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED• Am I aware of the basics of scientific writing required to write an informative report?• Do I remember the basics of mathematics?• How do I use statistics to plan and analyze my field or experimental data?• How to lose the fear of using a spreadsheet?• How to do basic repetitive calculations?• How to present figures and reports in scientific style?• How to efficiently select and summarize sub-groups of data?